Middle ear adenoma with neuroendocrine differentiation: relate of two cases and literature review - Bittencourt, Aline Gomes; Tsuji, Robinson Koji; Cabral, Francisco, Junior; Pereira, Larissa Vilela; Fonseca, Anna Carolina de Oliveira; Alves, Venâncio; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2013)
Introduction: Adenomas with neuroendocrine differentiation are defined as neuroendocrine neoplasms, and they are rarely found in the head and neck.Objective: To describe two cases of a middle ear adenoma with neuroendocrine differentiation, with a literature review.Case Report: Patient 1 was a 41-year-old woman who presented with a 3-year history of left aural fullness associated with ipsilateral “hammer beating” tinnitus. Patient 2 was a 41-year-old male who presented with unilateral conductive hearing loss.Conclusion: Adenoma with neuroendocrine differentiation of the middle ear is a rare entity, but it should be considered in patients with tinnitus, aural fullness, and a retrotympanic mass and remembered as a diferential diagnosis of tympanic paraganglioma.
Keywords: Neuroendocrine Tumors; Hearing Loss; Adenoma